2010
DOI: 10.1200/jco.2009.23.4278
|View full text |Cite
|
Sign up to set email alerts
|

Transition of Care for Young Adult Survivors of Childhood and Adolescent Cancer: Rationale and Approaches

Abstract: A B S T R A C T PurposeYoung adult survivors of childhood and adolescent cancer are an ever-growing population of patients, many of whom remain at lifelong risk for potentially serious complications of their cancer therapy. Yet research shows that many of these older survivors have deficient health-related knowledge and are not engaging in recommended health promotion and screening practices that could improve their long-term outcomes. The purpose of this review is to address these disparities by discussing ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
160
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(165 citation statements)
references
References 51 publications
4
160
0
1
Order By: Relevance
“…3,4 In the Childhood Cancer Survivor Study cohort of over 14,000 survivors, two thirds had at least one chronic condition (e.g., second malignancy, premature cardiovascular disease, endocrinopathy) 25 years postdiagnosis; 3,[5][6][7][8] about half develop a severe or disabling chronic condition. 2,9 Survivors are at increased risk of psychosocial distress (e.g., anxiety, depression, post-traumatic stress), and many have neurocognitive dysfunction.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…3,4 In the Childhood Cancer Survivor Study cohort of over 14,000 survivors, two thirds had at least one chronic condition (e.g., second malignancy, premature cardiovascular disease, endocrinopathy) 25 years postdiagnosis; 3,[5][6][7][8] about half develop a severe or disabling chronic condition. 2,9 Survivors are at increased risk of psychosocial distress (e.g., anxiety, depression, post-traumatic stress), and many have neurocognitive dysfunction.…”
mentioning
confidence: 99%
“…7,[15][16][17][18] At different centers, LTF is offered during oncology clinic, on designated survivors' days in oncology clinic space, and in free-standing programs with their own space and staff. 19 Regardless of how it is structured, providing LTF is resource-intensive.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[27] It is widely acknowledged that transition of care is a top priority in ensuring ongoing health benefits to AYA patients. [28] It has been shown that dedicated, well structured transition models that include education to the AYA patient improve quality of life (QoL) health outcomes, Better health outcomes are probably observed because of the improvement in understanding of disease enabled by the education arms of the models, and improved compliance with clinic appointments facilitated by a model that continues to build patient and physician rapport. Despite the multiple benefits to the AYA patient seen with early transition programs, there are still multiple challenges in achieving smooth transition.…”
Section: Discussionmentioning
confidence: 99%